From barriers to boosters: initial teacher education for inclusive science education - Fränkel, Silvia; Sterken, Moritz; Stinken-Rösner, Lisa (Frontiers in Education, 2023)
The paper presents a literature review on current barriers and boosters in the context of initial science teacher education for inclusion. The authors argue that current science teacher education programs for prospective teachers could be improved by adopting a more conceptually grounded and sustainable approach towards inclusion. To this end, the paper proposes an approach based on inclusive values and evidence-based practices that would benefit all students. Firstly, the paper identifies several barriers that exist in current science teacher education programs, including the dominance of an add-on approach, separate teacher education tracks, and inadequate preparation for the topic leading to decreasing self-efficacy towards inclusion. Secondly, to overcome these barriers, the paper proposes the integration of evidence-based practices, collaboration, and knowledge-transfer in science teacher education programs. These boosters can equip prospective science teachers with the necessary skills and knowledge for effective inclusive science education. Overall, the paper provides valuable insights and recommendations for improving initial science teacher education programs in the context of inclusion.